Review: Formulasi Optimum Sediaan Gel Lidah Buaya (Aloe Vera L.) serta Efektifitasnya Sebagai Obat Luka Pada Hewan Uji - Rahayuni, Ni Putu Dewi; I Wayan Martadi Santika (Program Studi Akuntansi IKOPIN, 2022)
Gel preparations are good topical treatments for inflammation. Aloe Vera (Aloe Vera) can be used topically to treat wounds in the form of a gel dosage because it contains mannose-6-phosphate and polysaccharides which function as wound medicine. To obtain the optimum formulation for Aloe Vera gel (Aloe Vera L.) and its effectiveness as a wound medicine in tested animals. Aloe Vera activity as wound healing formulated as a gel preparation for Aloe Vera (Aloe Vera L.) showed that it was able to reduce the size of the burn area on a 5% Na-CMC basis. The Na-CMC based gel formulation had a better speed than the Karbopol-based gel formulation in healing burns.